Managing Underwriters and the Marketing of Seasoned Equity Offerings - Huang, Rongbing; Zhang, Donghang (Journal of Financial and Quantitative Analysis, 2011)
Abstract Using a sample of 2,281 seasoned equity offerings (SEOs) from 1995 to 2004, we show that the marketing of securities is important to issuers. The number of managing underwriters for an SEO is negatively related to the offer price discount, especially when the relative offer size is large and the stock return volatility is high. Larger investor networks of comanaging underwriters also lower offer price discounts. We argue that the evidence is supportive of the marketing hypothesis: The underwriters’ marketing efforts can lower the offer price discount by shifting up and flattening the demand curve of an SEO.